Dermis layer injection containing microspheres
By using hyaluronic acid hydrogel with suitable crosslinking as the matrix and adding microspheres of appropriate particle size, the problem of microspheres settled in the injection agent is solved, and the stability and fluidity of the dermal injection agent are achieved, and it is suitable for 32G or 34G needle injection.
Patent Information
- Application Number
- CN202411991067.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-21
AI Technical Summary
In existing dermal injections, microspheres are prone to settle or agglomerate in low viscosity hydrogels, resulting in needle blocking problems and making it difficult to obtain stable injections.
Use hyaluronic acid or hyaluronic acid hydrogel with a crosslinking degree of 1% to 5% as the matrix, add microspheres of appropriate particle size, and adjust the ratio of crosslinking agent and alkali liquid to ensure that the microspheres are evenly dispersed in the injection agent and avoid settlement.
The stable dispersion of microspheres in the injection agent is achieved, the needle blocking problem is avoided, the fluidity and stability of the injection agent are ensured, and the injection can be injected through a 32G or 34G needle.
Smart Images

Figure CN119656384A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of medical cosmetology, specifically, to a dermal injection, and more specifically to a dermal injection containing microspheres. Background Art
[0002] In recent years, medical cosmetology has evolved from simple filling to regeneration, that is, by injecting microspheres into the subcutaneous tissue to stimulate the patient to produce collagen, so as to achieve the purpose of long-term wrinkle removal. When microspheres are added to the injection, they will stimulate the subcutaneous fibroblasts to produce collagen.
[0003] Dermal injection, also known as intradermal injection, is a medical cosmetic method that directly injects nutrients into the dermis, which can improve the appearance of the skin. Depending on the type and amount of the injection, it can have whitening and wrinkle removal effects. Dermal injections are also called water light needles. Generally, a 32G needle is used, with an inner diameter of 0.10mm and an outer diameter of 0.23mm. Some products use a smaller diameter 34G needle, with an inner diameter of 0.06mm and an outer diameter of 0.23mm. Needles with smaller diameters leave smaller pinholes, less pain, less bleeding, and faster recovery after injection, but they have higher requirements for injections and are prone to needle blockage.
[0004] Although fibroblasts also exist in the dermis, adding microspheres to the hydration injection can theoretically stimulate fibroblasts to produce collagen and achieve the effect of long-term filling of fine wrinkles, but there are currently no hydration injection products with microspheres on the market. The main technical difficulty is that the hydration injection uses microneedles to inject a small amount of fluidity and low viscosity, and the microspheres are easy to settle or agglomerate in low-viscosity hydrogels, causing needle blockage, making it difficult to obtain a stable dermis injection.
[0005] Hyaluronic acid, also known as hyaluronic acid, is a commonly used filler in medical cosmetology. Because it metabolizes quickly in the body, cross-linked hyaluronic acid is often used as a subcutaneous filler. The higher the degree of cross-linking, the slower the metabolism in the body. Hyaluronic acid with a cross-linking degree of more than 10% or even more than 20% is generally used in subcutaneous injection fillers.
[0006] CN108047351A discloses a method for preparing sodium hyaluronate with a low cross-linking degree. In the examples, slightly cross-linked hyaluronic acid with a cross-linking degree of 0.88% to 1.84% is prepared, and it is recorded that it can meet the needs of multiple fields such as medicine, beauty, and cosmetics for different purposes. However, it does not disclose its combination with microspheres or examples of intradermal injection.
[0007] CN114621501A discloses a variety of hyaluronic acid with a cross-linking degree of 3.23-9.76, and an elastic modulus of more than 500Pa. The technical effect is that the deep injection effect is more three-dimensional and the supporting performance is more excellent.
[0008] CN113230451A discloses a skin injection containing polyester materials, sodium hyaluronate and a dispersant, and records that it is also suitable for superficial dermal water injection to fill shallow wrinkles. It uses a higher dose of mannitol or amino acid dispersant to avoid microsphere sedimentation, resulting in excessive osmotic pressure of the product, which can cause injection pain and inflammatory reactions.
[0009] CN118356370A discloses a degradable microsphere controlled-release agent encapsulating a water light needle solution for facial dermal injection, but only discloses the preparation method of the microspheres, and does not explain how to prepare a dermal injection. Summary of the invention
[0010] In order to solve the above problems, the present application proposes a dermal injection, which is a hydrogel, and the hydrogel includes hyaluronic acid or hyaluronate with a cross-linking degree of 1% to 5%. Microspheres are dispersed in the hydrogel. The injection can pass through a 32G microneedle. As a further preference, the injection can pass through a 34G microneedle.
[0011] In this application, to be able to pass through a 32G microneedle, all microspheres are required to have a particle size of no greater than 75 μm; to be able to pass through a 34G microneedle, all microspheres are required to have a particle size of no greater than 50 μm. Microspheres with a particle size that is too large may cause needle blockage.
[0012] As is common knowledge in this field, sieving methods can be used to obtain particles with a maximum particle size not exceeding 75μm and 50μm. When the requirements are not strict, the commonly used 75μm sieve and 50μm sieve in the process can be directly selected, or a sieve with a specific aperture can be specially customized.
[0013] The cross-linking degree of the hyaluronic acid or hyaluronate is more preferably 2% to 4%.
[0014] Preferably, the content of the hyaluronic acid or hyaluronate is 0.2wt%-2.5wt%.
[0015] Preferably, the elastic modulus of the dermal injection is ≤80 Pa, and the viscosity is ≤300 Pa·s.
[0016] Preferably, the microspheres are microspheres that can be used for injection into the dermis and / or subcutaneous tissue in medicine, and the maximum particle size of the microspheres does not exceed 75 μm. As a further preference, the injection can pass through a 34G microneedle, and the maximum particle size of the microspheres does not exceed 50 μm. The microspheres are selected from one or more of polycaprolactone (PCL), poly-L-lactic acid (PLLA), poly-racemic lactic acid (PDLLA), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), polydioxanone (PDO), poly-L-lactic acid-ethylene glycol (PLLA-PEG), and hydroxyapatite (HAP), with a content of 0.1% to 5%, preferably 0.5% to 3%.
[0017] The present application also provides a method for preparing the above-mentioned dermal injection, characterized in that it comprises at least the following steps: (1) cross-linking hyaluronic acid or hyaluronate with a cross-linking agent; washing to remove the cross-linking agent after cross-linking, and then grinding or pulverizing to prepare a gel; (2) Adding polymer microspheres to the gel for blending, stirring evenly, and producing a dermal injection through terminal sterilization or aseptic process.
[0018] The reaction temperature required when using different cross-linking agents belongs to the prior art. The cross-linking agents and alkali solutions required to achieve a specific degree of cross-linking are different. Those skilled in the art can adjust them by themselves through simple parallel experiments, which are not listed here one by one.
[0019] The present application also provides an injection needle, which includes a needle and a needle tube, wherein the needle is a 32G or thinner needle, such as a 34G needle, and the dermis injection is encapsulated in the needle tube.
[0020] In the hydrogel of the present application, in addition to water and hyaluronic acid or hyaluronate, small molecule substances, such as osmotic pressure regulators such as NaCl, and nutrients such as amino acids, may be optionally added.
[0021] In this application, unless otherwise specified, the content refers to weight percentage, i.e. wt%.
[0022] In this application, the method for detecting the degree of crosslinking refers to the method described in the document Carbohydrate Polymers 91 (2013) pp. 410-418, and the steps are as follows: Place the prepared cross-linked sodium hyaluronate gel in pure water, stir for 1 hour, let it stand and settle, take out the gel and drain the water. Add the washed cross-linked sodium hyaluronate gel to pure water to swell for 30 minutes, add sodium hyaluronate enzyme, prepare a 200 IU / mL solution and shake well, incubate in a 37°C water bath for 24 hours, then boil, centrifuge to remove the enzyme, and freeze-dry to powder.
[0023] Dissolve the powder in D2O to form a test solution, and test the 1H NMR of the sample at 30°C. The MoD is determined by integrating the 1.6 ppm CH2 signal of different BDPE residues and the 2.0 ppm signal of the N-acetyl group of the disaccharide unit. The ratio of the integrals of these two signals (δ1.6ppm / δ2.0ppm) is the MoD value of the sample.
[0024] In this application, the elastic modulus detection method is exemplified as follows: At (25±2)°C, a rheometer is used to perform frequency sweep at a shear rate of 0.01 Hz to 100 Hz, and the elastic value at a frequency of 0.1 Hz is taken. As an example, the RS4SSTB230LS rheometer produced by Anton Paar is used in the examples of the present application.
[0025] In this application, the shear viscosity detection method is exemplified as follows: At (25 ± 0.2) °C, the rheometer was used to test the shear rate from 0.001s - ¹~1000s - ¹Perform peristaltic scanning, take 0.1s - ¹Viscosity value at shear rate.
[0026] The advantages of the technical solution of this application are: 1. The first microsphere-containing injection for dermal layer injection that can be stably stored was developed. After the injection is injected into the dermis, it can stimulate collagen regeneration; 2. The injection of the present application can pass through a 32G needle, preferably a 33G needle, and more preferably a 34G needle; 3. The present application adjusts the cross-linking degree of hyaluronic acid or hyaluronate, thereby preventing the microspheres from settling even at a lower viscosity.
[0027] 4. The injection of the present application has a low elastic modulus, and is not prone to causing skin bumps when injected into the dermis, and has no foreign body sensation when touched. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Other features, objects and advantages of the present application will become more apparent by reading the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 is a photograph of a hydrogel prepared according to an embodiment of the present application; Figure 2 This is a photo of an injection prepared according to an embodiment of the present application encapsulated in a manual syringe with a microneedle; Figure 3 yes Figure 2 Photograph of the syringe shown mounted on an automatic injection device; Figure 4 This is a photo taken immediately after 0.2 mL of hydrogel was injected into the dermis of a rabbit in animal experiment 1; Figure 5-6 This is a photo of the process of bulge disappearance after 0.2 mL of hydrogel was injected into the dermis of rabbits in animal experiment 1; Figure 7 This is a photo of the complete disappearance of the bulge (no bumpiness visually and by hand) after 0.2 mL of hydrogel was injected into the dermis of the rabbit in animal experiment 1; Figure 8 This is a photo of the animal experiment 2 after 0.2 mL of hydrogel was injected into the dermis of the rabbit; Figure 9-10 This is a photo of the process of bulge disappearance after 0.2 mL of hydrogel was injected into the dermis of rabbits in animal experiment 2; Fig.11 This is a photo of the complete disappearance of the bulge (no bumps and depressions visible or felt by hand) after 0.2 mL of hydrogel was injected into the dermis of a rabbit in animal experiment 2; Fig.12 This is a blank group photo of skin tissue sections from the uninjected area in animal experiment 3; Fig.13 This is a group of photos of skin tissue slice samples at the injection site 26 weeks after the injection in animal experiment 3; Fig.14 It is a photo of the microspheres being able to disperse evenly without stratification; Fig.15 is a photo of microsphere stratification. DETAILED DESCRIPTION
[0029] In order to better understand the present application, the technical solution of the present application will be described in more detail with reference to the accompanying drawings. It should be understood that these detailed descriptions are only descriptions of exemplary embodiments of the present application and are not intended to limit the scope of the present application in any way. Throughout the specification, the same reference numerals refer to the same elements. The expression "and / or" includes any combination or all combinations of one or more items in the associated listed items.
[0030] In the accompanying drawings, the size, proportions and shapes of the figures have been slightly adjusted for ease of illustration. The drawings are for illustration only and are not drawn strictly to scale. As used herein, the terms "substantially," "approximately," and similar terms are used as terms of approximation, not degree, and are intended to account for the inherent deviations in measurements or calculations that would be recognized by one of ordinary skill in the art.
[0031] It should also be understood that expressions such as "including", "comprising", "having", "containing" and / or "comprising" in this specification are open rather than closed expressions, which indicate the presence of the stated features, elements and / or parts, but do not exclude the presence of one or more other features, elements, parts and / or combinations thereof. In addition, when an expression such as "at least one of..." appears after a list of listed features, it modifies the entire list of features rather than just a single feature in the list. In addition, when describing embodiments of the present application, "may" is used to mean "one or more embodiments of the present application". And, the wording "exemplary" is intended to refer to an example or illustration.
[0032] Unless otherwise defined, all words (including engineering terms and scientific and technological terms) used in this article have the same meaning as those commonly understood by ordinary technicians in the field to which this application belongs. It should also be understood that unless there is a clear explanation in this application, words defined in commonly used dictionaries should be interpreted as having the same meaning as their meaning in the context of the relevant technology, and should not be interpreted in an idealized or overly formal sense.
[0033] It should be noted that, in the absence of conflict, the features in the embodiments and examples of the present application can be combined with each other. In addition, unless explicitly limited or contradictory to the context, the specific steps included in the method described in the present application are not necessarily limited to the order described, but can be performed in any order or in parallel. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0034] The inventors found in the study that the molecular weight of sodium hyaluronate of 200,000-2 million has basically no effect on stability. Using sodium hyaluronate of different molecular weights commonly used in the medical beauty field or one or more of the common cross-linking agents BDDE (1,4-butanediol diglycidyl ether), PDE (polyethylene glycol epoxy ether), PEG (polyethylene glycol), ADH (adipic acid dihydrazide), PEGDE (polyethylene glycol diglycidyl ether) for compounding, under the condition of the same degree of cross-linking, there is no obvious difference in the stratification stability of the preparation. Therefore, the most common sodium hyaluronate with a molecular weight of 1.26 million is used in the embodiment. The sodium hyaluronate used in the embodiment of this application was purchased from Huaxi Biotechnology Co., Ltd., with a molecular weight of 1.26 million, and the cross-linking agent is BDDE, which was purchased from Sigma.
[0035] Hydroxyapatite in the embodiment is purchased from Beijing Dekedao Gold. Preparation method of polycaprolactone, poly-L-lactic acid, poly-racemic lactic acid, polymethyl methacrylate: take a suitable proportion of polyvinyl alcohol and dissolve it in water, as an aqueous phase solution for standby, take polycaprolactone / poly-L-lactic acid / poly-racemic lactic acid / polymethyl methacrylate / poly-L-lactic acid-ethylene glycol raw materials, dissolve them in dichloromethane according to a suitable proportion, transfer them to a flask after complete dissolution, pour the aqueous phase solution, seal and stir until microspheres of suitable particle size are obtained, stop stirring, remove the solvent and the aqueous phase solution, clean and dry, encapsulate the dried microspheres, and sterilize by irradiation. There are many literature reports on the preparation method of microspheres, and there are also many commercially available products. Those skilled in the art can prepare or purchase microspheres of suitable particle size by themselves, and sieve out large-size microspheres that may cause needle blocking.
[0036] Example 1
[0037] 3g of sodium hyaluronate was added to 20g of sodium hydroxide solution with a mass concentration of 1%, and 0.05g of a cross-linking agent was added to mix well, and the mixture was reacted at 30°C for 18h; the cross-linked gel was washed to remove the cross-linking agent, and then ground or pulverized to granulate. The prepared micro-cross-linked sodium hyaluronate gel had a cross-linking degree of 3.12%.
[0038] Take 98.5 g of the micro-cross-linked sodium hyaluronate gel prepared by the above method into a beaker, add 1.5 g of polycaprolactone microspheres, the weight-average molecular weight of the microspheres is 21.5 kDa, the average particle size is 31 μm, stir evenly, and obtain the composite material for injection of this product, with an elastic modulus of 4.05 Pa·s, a viscosity of 42.5 Pa·s, and a sodium hyaluronate content of 12 mg / g.
[0039] Example 2
[0040] 3g of sodium hyaluronate was added to 25g of 1% sodium hydroxide solution, and 0.02g of cross-linking agent was added and mixed, and reacted at 30°C for 18h. The cross-linked gel was washed to remove the cross-linking agent, and then ground or pulverized to granulate. The prepared micro-cross-linked sodium hyaluronate gel had a cross-linking degree of 1.07%.
[0041] Take 99.9 g of the micro-cross-linked sodium hyaluronate gel prepared by the above method into a beaker, add 0.1 g of poly-L-lactic acid microspheres, the weight-average molecular weight of the microspheres is 5.87 kDa, the average particle size is 16 μm, stir evenly, and obtain the composite material for injection of this product, with an elastic modulus of 0.33 Pa·s, a viscosity of 4.21 Pa·s, and a sodium hyaluronate content of 2 mg / g.
[0042] Example 3
[0043] 3g of sodium hyaluronate was added to 18g of 1% sodium hydroxide solution, and 0.07g of cross-linking agent was added and mixed, and reacted at 30°C for 18h. The cross-linked gel was washed to remove the cross-linking agent, and then ground or pulverized to granulate. The prepared micro-cross-linked sodium hyaluronate gel had a cross-linking degree of 4.22%.
[0044] Take 95g of the micro-cross-linked sodium hyaluronate gel prepared by the above method into a beaker, add 5g of polycaprolactone microspheres, the weight-average molecular weight of the microspheres is 208kDa, the average particle size is 60μm, stir evenly, and obtain the composite material for injection of this product, with an elastic modulus of 79.8Pa·s, a viscosity of 295.2Pa·s, and a sodium hyaluronate content of 25mg / g.
[0045] Example 4
[0046] 3g of sodium hyaluronate was added to 20g of 1% sodium hydroxide solution, and 0.02g of cross-linking agent was added and mixed, and reacted at 30°C for 18h. The cross-linked gel was washed to remove the cross-linking agent, and then ground or pulverized to granulate. The prepared micro-cross-linked sodium hyaluronate gel had a cross-linking degree of 1.52%.
[0047] Take 99.5 g of the micro-cross-linked sodium hyaluronate gel prepared by the above method into a beaker, add 0.5 g of poly-L-lactic acid microspheres, the weight-average molecular weight of the microspheres is 122 kDa, and the average particle size is 18 μm, stir evenly, and obtain the composite material for injection of this product, with an elastic modulus of 1.48 Pa·s, a viscosity of 4.53 Pa·s, and a sodium hyaluronate content of 5 mg / g.
[0048] Example 5
[0049] 3g of sodium hyaluronate was added to 20g of 1% sodium hydroxide solution, and 0.04g of cross-linking agent was added and mixed, and reacted at 30°C for 18h. The cross-linked gel was washed to remove the cross-linking agent, and then ground or pulverized to granulate. The prepared micro-cross-linked sodium hyaluronate gel had a cross-linking degree of 2.23%.
[0050] Take 99g of the micro-cross-linked sodium hyaluronate gel prepared by the above method into a beaker, add 1g of polymethyl methacrylate microspheres, the weight-average molecular weight of the microspheres is 56kDa, the average particle size is 22μm, stir evenly, and obtain the composite material for injection of this product, with an elastic modulus of 4.21Pa·s, a viscosity of 17.35Pa·s, and a sodium hyaluronate content of 9mg / g.
[0051] Example 6
[0052] 3g of sodium hyaluronate was added to 19g of 1% sodium hydroxide solution, and 0.04g of cross-linking agent was added and mixed, and reacted at 30°C for 18h. The cross-linked gel was washed to remove the cross-linking agent, and then ground or pulverized to granulate. The prepared micro-cross-linked sodium hyaluronate gel had a cross-linking degree of 2.51%.
[0053] Take 99g of the micro-cross-linked sodium hyaluronate gel prepared by the above method into a beaker, add 1g of polymethyl methacrylate microspheres, the weight-average molecular weight of the microspheres is 107kDa, the average particle size is 36μm, stir evenly, and obtain the composite material for injection of this product, with an elastic modulus of 15.3Pa·s, a viscosity of 81.52Pa·s, and a sodium hyaluronate content of 15mg / g.
[0054] Example 7
[0055] 3g of sodium hyaluronate was added to 18g of 1% sodium hydroxide solution, and 0.052g of cross-linking agent was added and mixed, and reacted at 30°C for 18h. The cross-linked gel was washed to remove the cross-linking agent, and then ground or pulverized to granulate. The prepared micro-cross-linked sodium hyaluronate gel had a cross-linking degree of 3.57%.
[0056] Take 98g of the micro-cross-linked sodium hyaluronate gel prepared by the above method into a beaker, add 2g of polyracemic lactic acid microspheres, the weight-average molecular weight of the microspheres is 152kDa, the average particle size is 59μm, stir evenly, and obtain the composite material for injection of this product, with an elastic modulus of 45.4Pa·s, a viscosity of 188.22Pa·s, and a sodium hyaluronate content of 20mg / g.
[0057] Comparative Example 1 3g of sodium hyaluronate was added to 17g of 1% sodium hydroxide solution, and 0.09g of cross-linking agent was added and mixed, and reacted at 30°C for 18h. The cross-linked gel was washed to remove the cross-linking agent, and then ground or pulverized to granulate. The prepared micro-cross-linked sodium hyaluronate gel had a cross-linking degree of 6.02%.
[0058] Take 97g of the micro-cross-linked sodium hyaluronate gel prepared by the above method into a beaker, add 3g of polycaprolactone microspheres, the weight-average molecular weight of the microspheres is 21kDa, the average particle size is 31μm, stir evenly, and obtain the composite material for injection of this product, with an elastic modulus of 20.8Pa·s, a viscosity of 31.55Pa·s, and a sodium hyaluronate content of 12mg / g.
[0059] Comparative Example 2 Add 6 g of sodium hyaluronate into 194 g of phosphate buffer and stir at a low speed for 2-3 hours to obtain a sodium hyaluronate solution.
[0060] 98.5 g of the sodium hyaluronate solution prepared by the above method was taken into a beaker, and 1.5 g of polycaprolactone microspheres were added. The weight average molecular weight of the microspheres was 21 kDa and the average particle size was 32 μm. The mixture was stirred evenly to obtain the composite material for injection of the product. The viscosity was 9.88 Pa·s and the sodium hyaluronate content was 30 mg / g. The elastic modulus of the product was too small to be accurately detected.
[0061] Comparative Example 3 3g of sodium hyaluronate was added to 30g of 1% sodium hydroxide solution, and 0.01g of cross-linking agent was added to mix well. The mixture was reacted at 30°C for 18h. The cross-linked gel was washed to remove the cross-linking agent, and then ground or pulverized to granulate. The prepared micro-cross-linked sodium hyaluronate gel had a cross-linking degree of 0.18%.
[0062] Take 98.5 g of the micro-cross-linked sodium hyaluronate gel prepared by the above method into a beaker, add 1.5 g of polycaprolactone microspheres, the weight-average molecular weight of the microspheres is 21 kDa, the average particle size is 34 μm, stir evenly, and obtain the composite material for injection of this product, with an elastic modulus of 0.05 Pa·s, a viscosity of 11.97 Pa·s, and a sodium hyaluronate content of 15 mg / g.
[0063] Table 1, product parameters of Examples 1-7 and Comparative Examples 1-3.
[0064]
[0065] Animal testing.
[0066] New Zealand rabbits weighing 2.2-2.6 kg were selected. Before the experiment, the animals were anesthetized with injection of xylazine hydrochloride injection and tiletamine hydrochloride injection and zolazepam hydrochloride. The rabbit hair on the back was shaved. During the experiment, the skin of the surgical area was disinfected with iodine according to routine surgical requirements. Three implantation points were selected at equal distances on both sides of the rabbit spine, and the test samples were implanted into the dermis / subcutaneous tissue.
[0067] Animal experiments 1.
[0068] Microneedle injection: The sample is connected to an electronic syringe (water light instrument) and a microneedle, and 0.2 mL (nine needles, 9 needles for a total of 0.2 mL) is injected into the dermis each time (intradermal injection).
[0069] After injection, observe the injection site (see Figure 4 ), if there is no redness, swelling or bulge after a period of time, it proves that the micro-cross-linked material has good compatibility with the skin. Figure 5-7In this experiment, there was no redness or swelling at the injection site of all the products in the examples during the observation period, and no bulge after 72 hours. Redness and swelling were observed after injection in Comparative Example 1, and Comparative Examples 2 and 3 were unstable and were not injected. The above experimental results prove that the dermal injection prepared in the examples of the present application has good safety.
[0070] Animal experiments 2.
[0071] Hand injection: (single 32G needle) 0.2mL is injected at each point, intradermally. Observe regularly. It is required that the injection site should not be raised more than 1mm after a period of injection.
[0072] This experiment is used to observe the speed at which the material is absorbed. After the injection of the water light needle, the speed at which the bulge disappears directly affects the patient experience. Because the injection volume in animal experiment 1 was small and difficult to observe, the injection volume was increased and observed every 4 hours. Figure 8 - Fig.11 The process of relief is shown, and the time for skin relief to resolve (animal-evaluated flattening time) was recorded.
[0073] As shown in Table 2, the products of Examples 1-7 of the present application can all be laid flat within 48 hours, while Comparative Example 1 with a high degree of crosslinking requires more than 7 days, which may cause the patient's face to have a long-term uneven feeling when used for water light injection, affecting the appearance. This proves that the present application has achieved good technical effects by controlling the degree of crosslinking.
[0074] Animal experiments 3.
[0075] The animals were euthanized 26 weeks after injection, the implantation site was observed with the naked eye, and sufficient unaffected tissues including the implanted sample and the surrounding area were cut and fixed in 10% formalin fixative for no less than 48 hours. After sufficient fixation, tissue sections were made, and the tissue sections stained with Masson were observed under an optical microscope, and the collagen content was compared with that of tissues injected with normal saline.
[0076] Animal experiment 3 showed that the tissue section sample group injected with the composite material into the dermis (see Fig.13 ) and blank control (see Fig.12 ), the blue-stained collagen fibers in the dermis were thicker and more densely arranged, and the positive area ratio of the sample group was 60.6005%, which was much higher than the 47.6906% of the blank group. This proves that the composite material can promote the production of new collagen in the body, stimulate tissue collagen regeneration, and generate collagen fiber network.
[0077] Stratification stability test.
[0078] 1. Fill the prepared composite material for injection into a 1.0 mL prefilled syringe with a filling volume of 1.0 g / syringe. Place the filled sample vertically in a 40°C stability incubator. Take it out for observation after 6 months, record the product status, and observe whether there is stratification.
[0079] 2. Fill the prepared composite material for injection into a 1.0mL pre-filled syringe with a filling volume of 1.0g / syringe, and observe its stability by centrifugation. Place it in a suitable adapter, set the centrifugal speed to 4000r / min, and the time is 3min. After the centrifugation stops, take out the sample and observe whether it has stratification.
[0080] In both of the above methods, the product is not layered (see Fig.14 ) is considered to meet the requirements, otherwise it is considered unstable (see Fig.15 ).
[0081] Table 2 Animal experiment results and stability test of examples and comparative examples
[0082] As can be seen from Table 2, the paving time of Comparative Example 1 is greater than 7 days, which is much higher than that of Examples 1-7, indicating that excessive cross-linking is not conducive to paving, and the patient's skin bulges for too long when used for water light injection. Comparative Examples 2 and 3 show that no cross-linking or a small degree of cross-linking cannot prevent the microspheres from settling, and stratification will occur.
[0083] The above description is only an implementation method of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of protection involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the technical concept. For example, the above features are replaced with the technical features with similar functions disclosed in this application (but not limited to) by each other.
Claims
1. A dermal injection, characterized in that: The injection is a hydrogel, which includes hyaluronic acid or hyaluronate with a cross-linking degree of 1% to 5%. Microspheres are dispersed in the hydrogel, and the injection can pass through a 32G microneedle.
2. The dermal injection according to claim 1, characterized in that: The injection can pass through a 34G microneedle.
3. The dermal injection according to claim 1, characterized in that: The cross-linking degree of the hyaluronic acid or hyaluronate is 2% to 4%.
4. The dermal injection according to claim 1, characterized in that: The content of the hyaluronic acid or hyaluronate is 0.2wt%-2.5wt%.
5. The dermal injection according to claim 1, characterized in that: The elastic modulus of the dermal injection is ≤80Pa, and the viscosity is ≤300Pa·s.
6. The dermal injection according to claim 1, characterized in that: The microspheres are microspheres that can be used for injection into the dermis and / or subcutaneous tissue in medicine.
7. The dermal injection according to claim 6, characterized in that: The maximum particle size of the microspheres does not exceed 75 μm.
8. The injection according to claim 6, characterized in that: The injection can pass through a 34G microneedle, and the maximum particle size of the microspheres does not exceed 50 μm.
9. The dermal injection according to claim 6, characterized in that: The microspheres are selected from one or more of polycaprolactone, poly-L-lactic acid, polyracemic lactic acid, polyvinyl alcohol, polymethyl methacrylate, polydioxanone, poly-L-lactic acid-ethylene glycol, and hydroxyapatite.
10. The dermal injection according to claim 6, characterized in that: The content of the polymer microspheres is 0.1% to 5%, preferably 0.5% to 3%.
11. A method for preparing the dermal injection according to any one of claims 1 to 10, characterized in that: At least the following steps are included: (1) cross-linking hyaluronic acid or hyaluronate with a cross-linking agent; washing to remove the cross-linking agent after cross-linking, and then grinding or pulverizing to prepare a gel; (2) Adding polymer microspheres to the gel for blending, stirring evenly, and producing the dermal injection through terminal sterilization or aseptic process.
12. An injection needle, comprising a needle and a needle tube, wherein the needle is a 32G or thinner needle, and the dermal injection according to any one of claims 1 to 10 is encapsulated in the needle tube.
Citation Information
Patent Citations
Preparation method of sodium hyaluronate with low crosslinking degree
CN108047351A
Injectable skin filler and preparation method thereof
CN113230451A
Degradable microsphere controlled release agent entrapped with hydro-optical needle solution as well as preparation method and application of degradable microsphere controlled release agent
CN118356370A